(untitled) (Revista de Ciências Agroveterinárias, 2011)
When the soil management does not include significative soil disturbation, like in no tillage system, the lime is applied on the surface, without incorporation. To study the effect, along the time, of a unique superficial application of lime doses on the soil chemical characteristics and on crop production, it was conducted a trial in an Oxisol in Campos Novos Council, Santa Catarina State, Brazil. The treatments were lime doses of 0.0, 4.3, 5.8, 8.7 and 17.3 t ha-1, adjusted to 100% efficiency of a dolomite lime, which represents respectively doses of 0, 25, 33, 50 and 100% the need to increase soil pH in water to 6.0 at the 0-20 cm soil layer, calculated by the SMP index. The trial was performed along eight years, using a two years crop rotation including triticale (X Triticosecale, W.), soybean (Glicyne Max, L.), common wetch (Vicia sativa, L.) and corn (Zea mays, L.). It were evaluated, at the layers of 0.0-2.5, 2.5-5.0, 5.0-10.0 and 10.0-20.0 cm depth, the soil pH in water and exchangeable Al in eight sampling times, and exchangeable Ca and Mg in four sampling times, as well as relative grain production of triticale, soybean and corn whiting each harvest. The superficial lime application changed soil characteristics along of evaluation time, with increasing in soil pH in water, exchangeable Ca and Mg and level saturation by bases, and decreasing of exchangeable and level saturation by Al, at the beginning until 2.5 cm deep and decreasing down with time. The dose of 4.3 t ha-1 resulted in improvement of soil chemical characteristics, resulting in relative grain production of 90% to the soybean, in the medium of four harvests, and of 86 and 89% to the corn production, respectively in the fifth and seventh years after lime application.